Optimized conditions for determination of total soil organic matter in diverse samples by mass loss on ignition. Issue 6 (10th October 2014) - Ghabbour, Elham A.; Davies, Geoffrey; Cuozzo, Nicolas P.; Miller, Robert O.
Abstract: Reliable measurement of soil organic matter (SOM) contents is crucial to assessment of soil health, productive longevity and the effects of climate change. In this study, the loss‐on‐ignition (LOI) method has been used to determine the SOM of dried soil samples with a wide range of clay, sand and silt contents from the Agricultural Laboratory Proficiency (ALP) program. Regressions of ALP participant data against LOI measurements at 350–650°C indicate that the extent of SOM oxidation depends more on the ignition temperature and time than on the sample compositions. Thus, LOI data from ignition at 350–550°C for 12 h relative to ignition at 650°C for 12 h converge at 650°C and the average coefficient of variance decreases to ≈ 4% at 650°C. Also examined are regressions of soil organic C from direct dry combustion as standards with LOI measured at 360°C for 2 h, LOI measured at 650°C for 12 h and with the Walkley‐Black procedure used in the ALP program.